Evaluating the reinforcements efficiency of sawdust and corncob wastes in structural concrete: A comprehensive review - Abiodun Kilani; Ademilade Olubambi; Bolanle Ikotun; Oladipupo Oladejo; Babatunde Famodu (Journal of Building Materials and Structures)
Sawdust (SD) and Corncob (CC) wastes possess up to 89.4% and 83.03% pozzolanic properties with a high impact on the mechanical properties required for high concrete strength reinforcement respectively. Applications of SD and CC wastes in concrete increased the concrete workability by 8.75% and 27.9% respectively. In addition, the use of SD in concrete eased its aggregates’ compatibility rate by 4.4%. The consistency of cement paste with corncob ash (CCA) decreased with an increase in the percentage of CCA included. In addition, the final and initial setting times of paste with sawdust ash (SDA) decreased by 28.2% and 20% with increasing use in the percentage of SDA included, while that of CC increased with an increase in the percentage of CC. The densities of SDA-concrete and CCA – concrete observed were from 300 to 1800kg/m3 and 1998 kg/m3 to 2302kg/m3, and these were classified as lightweight concrete. The review showed that CCA had a high potential for increasing the concrete compressive strength by 34.5%. The blending of CC waste with other admixtures was observed to have increased concrete’s tensile properties by 3.9%. CC waste possessed high potential for composite tensile property enhancement up to 68%. The CCA-concrete’s flexural strength observed was low; the blending of CC with other admixtures has increased the concrete’s flexural strength. SDW-Concrete suggested to high temperature showed an increase in compressive strength until 6000C is reached, after 6000C, there was a reduction in strength. The CCA reduced concrete’s modulus of elasticity by 27%. From the X–ray result, quartz (SiO2) shows an essential and main mineralogical content of CCA. The concrete’s rate of water absorption increased by 74% with the inclusion of SD. The ANN model is efficient and possesses good features for CCA and SD – concrete models. In conclusion, SD and CC wastes possess a good potential for the enhancement of structural concrete, which can be processed into types of cement and concrete composites.